Faktor-Faktor Pemberian Kolostrum pada Ibu Post Partum di Desa Kayu Kul Kecamatan Pegasing Kabupaten Aceh Tengah Tahun 2022 - Desi Yuliana; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Agustina Susilawati Tumangger (Jurnal Ventilator, 2024)
Colostrum is the first fluid secreted by the mammary glands. The highest content in colostrum is antibodies that are ready to protect the baby when the baby is still very weak. The protein content in colostrum is higher than the protein content in mature milk. The purpose of this study was to analyze the factors of colostrum administration to postpartum mothers in Kayu Kul Village, Pegasing District, Central Aceh Regency in 2022. The method in this study is an analytical research type with a research design using cross-sectional, namely a study in which variables including risk factors and variables including effects are observed at the same time. This study uses data taken retrospectively. This research was conducted in Kayu Kul Village, Pegasing District, Central Aceh Regency in 2022. The population in this study was 35 people, then the sample was part of all the objects studied and was considered to represent the entire population (Notoatmodjo, 2015). The number of samples used was 29 people using the Accidental Sampling technique. Data collection techniques using questionnaire sheets and respondent observation sheets. Data analysis techniques using the chi-square statistical test show that the p-value shows that p = 0.005 which means Ho is accepted (p value <0.05), so it can be concluded that there is a significant relationship between the knowledge category and the provision of colostrum. Conclusion: This study means that there is a significant relationship between the factors of Knowledge, Family Support, Support, Information Sources, Parity, Role of Health Workers, Provision of Colostrum in Kayu Kul Village, Pegasing District, Central Aceh Regency in 2022.